Porto de moz: o prefeito, "dono do municipio" - Salgado, I.; Kaimowitz, D. (A.S. Editores, 2003)
Porto de Moz is a small municipality (22.460 inhabitants) bordered by the Xingu and Amazonas Rivers, in the state of Pará. The local economy is based on small-scale agriculture, fishing, and timber extraction. Land ownership is extremely concentrated, and a large part of the municipal lands are unclaimed and subject to land grabbing by fraudulent and violent means. Control over land is essential for the largest sawmills, which relies on illegal logging. The mayor and his relatives own three of the four local sawmills, and therefore have high stakes in the struggle for land. There are a few grassroots organizations in Porto de Moz whose members overtly oppose and try to resist the abuses of the municipal government. Among these efforts, they formed a “Natural Resource Municipal Committee” which laid plans for a more equitable and sustainable development model in the Municipality, but have never received any support from the local government. Federal and state agencies that could mediate the local conflicts are conspicuously absent from the municipality. The isolation and transportation problems contribute to this situation; however, the mayor’s effort to keep any authority that could interfere with his interests is evident. Porto de Moz is an extreme example of the excessive power that mayors have in the Brazilian system. Nevertheless, it does not mean that decentralization should be avoided, but rather that there must exist effective checks and balances on the local power to prevent this kind of abuse.